Kidney and Metabolic Phenotypes in Glycogen Storage Disease Type-I Patients - Aoun, Bilal; Sanjad, Sami; Degheili, Jad A.; Barhoumi, Abir; Bassyouni, Amina; Karam, Pascale E. (Frontiers in Pediatrics, 2020)
Glycogen storage disease type I (GSD- I) is a rare autosomal recessive disorder of glycogen and fat metabolism, leading to progressive accumulation of glycogen in major organs such as liver and kidneys. Variable stages of kidney disease from proximal and distal tubulopathies to irreversible glomerular injury may affect the outcome of GSD-I patients. Early detection of kidney complications, such as microalbuminuria, treatment with angiotensin converting enzyme inhibitors (ACEI) as well as optimal metabolic control have been suggested to delay or even prevent severe GSD-I kidney disease. The adequacy of metabolic control is usually assessed by glucose, lactic acid, triglycerides and uric acid blood levels. Obtaining accurate blood lactate levels can be challenging in children whereas plasma alanine level reflecting chronic lactic acidosis could play a role in the assessment of metabolic control. Patients and Methods A retrospective chart review of 32 GSD- I patients, followed at the American University of Beirut Medical Center, between 2007 and 2018 was conducted. Diagnosis was confirmed by enzymatic and/or genetic studies. Clinical presentation, growth and kidney outcome were assessed. All patients were evaluated for body mass index, blood parameters of metabolic control including uric acid, alanine, lactic acid and triglycerides in blood. Kidney evaluation included creatinine clearance, microalbuminuria, citraturia and calciuria as well as urine microalbumin/creatinine ratio. Results Almost one third of GSD-I patients developed microalbuminuria. This was detected below 7 months of age in 36% of patients who required early treatment with ACEI with significant reduction in albuminuria. Kidney stones were present in 6% and were associated with hypercalciuria and hypocitraturia. Poor metabolic control reflected by hyperuricemia, lactic acidosis and hyperalaninemia were noted only in patients who developed microalbuminuria. Conclusion Glomerular injury may appear in early infancy in poorly controlled patients. Adequate metabolic control and ACEI therapy may improve kidney outcome in GSD I patients. Plasma alanine appears to be a promising and reliable marker reflecting metabolic control in GSD-I patients.